(untitled) (REMUNOM, 2024)
Objective: this study aimed to present the socioepidemiological and pharmacological profile of the pregnant women receiving prenatal care at Hospital das Clínicas of UFPE. Methods: cross-sectional study carried out through direct interview with 330 pregnant women attended at high risk prenatal care at the HC/UFPE between April and June of 2017. Results: The medical practice at HC-UFPE agrees with the literature. This population of pregnant women presents predominantly grievances common to the group, such as obesity, diabetes and asthma. The main drugs used were antianemic drugs and it was noted the team cared to avoid the use of drugs that can put mom and/or fetus in risk. Conclusions: The results presented demonstrates similarities with those found in the literature in relation to the drug prescription, but they also reinforce the need for larger studies on the topic, as by outlining the social profile of these women and the most prevalent health problems, it is possible to plan educational interventions aimed at pregnant women to promote the rational use of medication, and educational activities to the health professionals, all looking at the improvement of the indicators of maternal and child health.